A comparison of ultrasound‐guided interscalene and supraclavicular blocks for post‐operative analgesia after shoulder surgery. Issue 4 (5th February 2017) - Kim, B. G.; Han, J. U.; Song, J. H.; Yang, C.; Lee, B. W.; Baek, J. S.
Abstract : Background: In contrast to interscalene block, there was little information regarding the analgesic efficacy of supraclavicular block for shoulder surgery. This study aimed to compare the analgesic efficacy and side effects of interscalene and supraclavicular blocks for shoulder surgery. Methods: Patients scheduled for shoulder surgery were assigned to receive either ultrasound‐guided interscalene ( n = 25) or supraclavicular block ( n = 24) with 20 ml of 0.375% ropivacaine. We assessed the duration of post‐operative analgesia as a primary outcome and pain scores, supplemental analgesia, diaphragmatic excursion, motor block, fingertip numbness, side effects, and patient satisfaction as secondary outcomes. Results: The duration of post‐operative analgesia was not statistically different between groups: 868 (800–1440) min for supraclavicular block vs. 800 (731–922) min for interscalene block (median difference −85 min, 95% CI, −283 to 3 min, P = 0.095). The incidence of diaphragmatic paresis was significantly lower in the supraclavicular block group compared with that in the interscalene block group, both at 30 min after the block (66.7% vs. 92%, P = 0.021) and in the post‐anaesthesia care unit (62.5% vs. 92%, P = 0.024). Motor block was higher in the supraclavicular block group in the post‐anaesthesia care unit, however, not at 24 h. Other secondary outcomes were similar for both groups. Conclusions: This study showed no statistically significant difference in the duration of post‐operative analgesia between the supraclavicular and interscalene blocks. However, the supraclavicular block was associated with a lower incidence of diaphragmatic paresis compared with that of the interscalene block after shoulder surgery.